Multimodal Treatment of Cystic Echinococcosis - Paramita, Anak Agung Ketut Yunita; Wibawa, I Dewa Nyoman (The Indonesian Society for Digestive Endoscopy, 2023)
Cystic echinococcosis is a zoonotic disease that is caused by the larval stages of cestodes species and belongs to the genus Echinococcus. Echinococcus granulosus (E. granulosus) causes cystic echinococcosis which is global and wider in its distribution than alveolar echinococcosis. Endemic areas of E. granulosus are Russia, Eastern Europe, the Middle East, China, and South America based on data from the World Health Organization (WHO). Incidence rates are 50 per 100,000 person-years. The life cycle of E. granulosus requires both an intermediate host and a definitive host. A human accidentally becomes an intermediate host. Upon infection, cyst formation mostly occurs in the liver (70%). At the first, the infection is usually asymptomatic. Diagnosis of cystic echinococcosis can be done by imaging techniques (ultrasound or CT/MRI), serum serologic testing for antibodies against hydatid antigens, and immunologic testing. In general, there are four different management modalities for cystic echinococcosis, such as surgery, percutaneous therapy surgery, chemotherapy, and watchful waiting.